Sujeitos em trânsito: espaços urbanos em Eles eram muitos cavalos, de Luiz Ruffato - Roberta Torres Trajano (2014)
Brazilian writer Luiz Ruffato has progressively earned a significant space in the literary scene in recent years. By providing us all with narratives which apply language experimentation as a means of discussing the small dramas of anonymous people, he has aroused the big interest of critics. The purpose of this work is to analyze Luiz Ruffatos There were many horses [eles eram muitos cavalos] having as keywords both the urban space of the referred text and the expressive paradigm of contemporary mobility. The concept of non-place coined by Marc Augé (1994) will be herein used as theoretical support, among other terms, which will be approached as reading pivots of sorts, such as subjects in transit, anonymity and non-person. The theme of violence that marks the postmodern individuals condition after tragic events is herein made explicit through a kind of performance writing that transgresses the structure of traditional novels, by breaking off with the idea of sentence continuity and standard syntax.